Temperature effect on the maximum swimming speed of jack mackerel Trachurus japonicus through muscle contraction monitoring - Nofrizal (2020)
The purpose of this study is to know the effect of temperature on fish muscle contraction of jack mackerel (Trachurus japonicus), which muscle contraction will determine the tail beat frequency and maximum swimming speed. The maximum swimming speed of was evaluated according to the measurement of the muscle contraction time with electric stimuli of 2-7 V, 50 ms. Fish were separated into four groups for temperature acclimation at 10, 15, 18 and 22 ºC to reflect typical changes in seasonal water temperature in Japan. Results showed that the swimming speed of the fish was positively related to the tail-beat frequency at all temperatures. The muscle contraction time was also affected by the acclimated temperature, which longer at the lower temperature than higher ones. Mean contraction time (Tm) was 45.1 ms at 10 ºC, 32.7 ms at 15 ºC, 32.9 ms at 18 ºC, and 31.9 ms at 22 ºC, respectively. The mean of maximum tail-beat frequency (Fmax) obtained from Fmax = ½ Tm was 11.4 Hz at 10 ºC, 15.8 Hz at 15 ºC, 16,4 Hz at 18 ºC, and 16.6 Hz at 22 ºC. These were used to estimate the maximum swimming speed (Umax) at each temperature, resulting in 9.45 FL s-1 at 10 ºC, 13.5 FL s-1 at 15 ºC, 14.0 FL s-1 18 ºC, and 14.2 FL s-1 at 22 ºC.  The seasonal temperature effects on the swimming performance of T. japonicus, which lower water temperature in the winter made low swimming performance.